Obesity and women's health: from menarche to menopause - Elena V Tsallagova; Vera N Prilepskaya (IP Berlin A.V., 2019)
The review is devoted to the problem of the influence of overweight and obesity on the health of a woman in different periods of life, in particular, on reproductive disorders resulting from exposure to adipose tissue.